COVID-19 and monkeypox co-infection: A rapid systematic review - Amr Ehab El-Qushayri; Abdullah Reda; Jaffer Shah (Frontiers in Immunology, 2022)
In this paper we aimed to study the characteristics, laboratory data and outcomes of monkeypox virus (MPV) and COVID-19 co-infection. On 2nd October 2022, we used the search term “(“monkeypox virus” OR “MPV” OR “monkey pox” OR “monkeypox”) AND (“COVID-19” OR “COVID 19” OR “novel coronavirus” OR “SARS−CoV−2”)” in five databases to collect the relevant articles. We found three male patients, who had sex with men prior to the infection, had multiple comorbid conditions, were diagnosed with PCR, and were admitted to the hospital. The length of hospital stay was 4, 6, and 9 days. On admission, two cases had multiple vesicular lesions on various sites of the body associated with tonsillar inflammation, while the third case had genital ulcers and inguinal lymph node enlargement. All cases were managed in the hospital and recovered well. It might still be too early to establish solid evidence about the exact cause-effect association between SARS-CoV-2 and MPV co-infection and patient’s outcomes because of the current low sample size. Accordingly, future relevant investigations, estimating the risk ratio of this association are needed to formulate definite evidence.